Factors affecting conception rates in heifers and cows synchronized with Syncro-Mate-B® - J.T. Brink; C.D. Middleton; G.H. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1985)
In five trials during 1983 and 1984, 238 cows and 54 heifers were synchronized with Syncro-Mate-B® and artificially inseminated 48 hours after implant removal. The conception rate was 42.5% in cows that were cycling and 19.8% in cows that were not cycling before Syncro-Mate-B® treatment. Heifers started on the Syncro-Mate-B® treatment before day 11 of the estrous cycle had a higher conception rate (64.3%) than heifers started after day 11 (38.5%). Conception rates among the trials varied from 19.8 to 64.3%.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Conception rates; Synchronized